The vein of gold. In search of a methodological renewal of dogmatics based on the reading of Lech Wołowski’s book entitled “The problematics of paradox in the thought of Henri de Lubac and Hans Urs von Balthasar” - Cezary Smuniewski (Polonia Sacra, 2024)
This study is presented in the form of a research-review article and consists of reflections informed by a reading of Lech Wołowski’s monograph “The Problematics of Paradox in the Thought of Henri de Lubac and Hans Urs von Balthasar”, while simultaneously drawing from other works by the same researcher. The aim of this article is to present the paradox method as a means to deepen theological research. This method is portrayed as a proposition that can be applied in theological research, much like in other scientific domains. This approach may contribute to addressing the contemporary crisis in dogmatics and serve in formulating responses to current “profound” questions posed by individuals and society.